2014
DOI: 10.1186/1476-511x-13-163
|View full text |Cite
|
Sign up to set email alerts
|

Improving heart function by modulating myocardiocyte autophagy: a possible novel mechanism for cardiovascular protection of high-density lipoprotein

Abstract: BackgroundHigh-density lipoprotein (HDL) has been shown to confer cardiovascular protection in clinical and epidemiologic studies. Emerging evidence suggests that many of the cardioprotective functions of HDL may be due to the phospholipid sphingosine-1-phosphate (S1P).Presentation of the hypothesisHDL-S1P binds to S1P receptors in the heart, activating PI3K/Akt signaling and myocyte survival. PI3K/Akt is a classic signaling modulator of autophagy. Excessive autophagy due to cell death and cardiomyocyte loss m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We found that mTOR activity was suppressed in response to I/R, which was a crucial step for autophagic cell death in cardiomyocytes. Although autophagy is thought to play a central role in regulating cell death and survival, our data suggest that excessive autophagy, such as increased formation of autophagosomes and autophagic flux can lead to cardiomyocyte cell death . Despite our finding that DSS activation of mTOR can reduce ischaemia‐induced autophagy and tissue injury, it remains unclear whether continuous mTOR activation acts as an endogenous survival signalling mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…We found that mTOR activity was suppressed in response to I/R, which was a crucial step for autophagic cell death in cardiomyocytes. Although autophagy is thought to play a central role in regulating cell death and survival, our data suggest that excessive autophagy, such as increased formation of autophagosomes and autophagic flux can lead to cardiomyocyte cell death . Despite our finding that DSS activation of mTOR can reduce ischaemia‐induced autophagy and tissue injury, it remains unclear whether continuous mTOR activation acts as an endogenous survival signalling mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…In the context of high-fat diet induced accumulation of lipids, the proper autophagic clearance has proven important in attenuating reactive oxygen species 2527 . The attenuation of the lipotoxic cardiomyopathy in pressure overload-induced heart failure 28 similarly demonstrates the importance of autophagy in clearing lipids in cardiac stress, a process regulated by oxidized phospholipids 29 .…”
Section: Metabolism and Autophagymentioning
confidence: 88%
“…Pompe’s disease, caused by a deficiency of glycogenic glycemic enzyme acid α-glucosidase, results from the accumulation of autophagosomes ( Fukuda et al, 2006 ). Previous studies have demonstrated that the expression of ATG16L1 in atherosclerosis is closely related to the instability of lesions on atherosclerotic plaques ( Wang and Ye, 2014 ). In the necrotic core and surrounding area of human atherosclerotic plaque, particularly the shoulder area, ATG16L1 protein is abundantly expressed, and ATG16L1 immunomarkers are mainly found in the plaque endothelial cells and foamy smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%